What Happened in Talaga Biru? A Study of Ecological Literature - Ramis Rauf; Sulmi Magfirah; Ridwan Ridwan; Afriani Ulya (Humanitatis : Journal of Language and Literature, 2024)
This work aims to provide a detailed account of the moral teachings conveyed in the North Halmahera Talaga Biru Folklore. This method of this study employs qualitative research. The data collection technique employs interviews, audio recordings, and a comprehensive review of relevant literature. On the other hand, analyzing data involves multiple steps, including data reduction, display, verification, and conclusion. The research results reveal two overarching messages: positive and negative. The good messages encompassed in the text are as follows: 1) hope, 2) struggle, 3) sacrifice, 4) loyalty, 5) cooperation, 6) cultural values, 7) patience, 8) friendship, and 9) religious values. On the other hand, the contrasting message conveys a sense of sorrow. Sadness is a negative emotion due to the excessive and unreasonable sadness depicted in the Talaga Biru mythology. The depicted grief revolves around the character Majojaru, who experiences profound sorrow and sheds tears for a continuous duration of three days and three nights, ultimately resulting in their demise. In addition, it is anticipated that this will contribute to the development of theoretical knowledge about the moral themes found in folklore from North Halmahera. Moreover, it can serve as a valuable resource for managing culturally and literarily oriented tourism. Furthermore, this study is anticipated to make a valuable contribution to endeavours aimed at enhancing public consciousness regarding the significance of conserving the adjacent natural environment as a habitat for all global ecosystems.